ISKHAK-KHAN - LIFE IN SAMARKAND (ACCORDING TO THE OFFICE OF THE GOVERNOR-GENERAL OF TURKESTAN) - Ergashev Bahtiyar Ergashevich, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to the history of the Russian Empire's diplomatic activity in Turkestan in the second half of XIX - beginning of XX centuries. The main object of the research is the study of the history of relations between the Governor-General of Turkestan and Afghanistan international relations. The subject is the study of the history of Afghan citizens in Iskhak-Khan, the representative of the Afghan ruling dynasty, who, due to domestic political events, ended up in Turkestan's territory. The primary sources for the article were the case of the Turkestan governorate general's office. The materials of the Central State Archive served as a proof base for disclosing the social and domestic lives of Afghans in Turkestan.